(untitled) (Research, Society and Development, 2020)
Brazilian public policies in comprehensive Special Education have monitored the teaching modality during recent years even though many difficulties still exist for their execution. In order to reveal its current condition, this paper has as aim at analyzing public policies for Special Education implemented in Brazil to identify the current trends and their objective stalemates. The research is bibliographic and documentary, and its methodological approach is qualitative. There were different forms to conceive Special Education, since the initial rejection and segregation acts until its institutionalization. Na integration period has started and nowadays the legal referrals are comprehensive ones. In Brazil, in midst 1990s, the right of students with disabilities to attend common schools was ensured in all the teaching levels. Legislation demonstrates historical advances obtained and advocates a comprehensive educational policy. However, the ongoing trends indicate a regression expressed by the current BNCC contents, extremely restricted regarding Special Education. Besides, real reveals the distance between what was proclaimed and what was effectively performed. The inference is that its concretization stumble upon structural limits, which come from the productive logic and social inequality which are characteristics of the current capitalist sociability.